Memoria y conflicto. Memorias en conflicto Intercambios metódicos y teóricos de experiencias locales latinoamericanas - Aranha, Patricia (Historamericana, 2022)
The articles in this compilation analyze from various disciplinary approaches a sample of local experiences around work for memory as well as their respective conflicts in Colombia, Mexico, El Salvador, Peru, Argentina and Chile.